Biodegradable cement augmentation of gamma nail osteosynthesis reduces migration in pertrochanteric fractures, a biomechanical in vitro study. (April 2021) - Bungartz, Matthias; Matziolis, Georg; Layher, Frank; Horbert, Victoria; Maslaris, Alexander; Brinkmann, Olaf
Abstract: Background: Cut-out of gamma nail often results from poor primary bone stability, suboptimal reduction (varus) and excentric placement of the head element which may lead to "instability" and frequently requires revision. Various studies have shown that augmentation with polymethylmethacrylate cement increases the primary stability of osteosynthesis. However, it has not yet been widely used in fracture treatment due to certain disadvantages, e.g., the lack of osteointegration, the formation of an interface membrane or the presence of toxic monomers. Few studies show that biodegradable bone cements increase the stability of osteosynthesis in different anatomical regions and therefore could be an alternative to polymethylmethacrylate cement in the treatment of pertrochanteric fractures. Methods: Two biomechanical situations were simulated using 24 Sawbones (simple and multifragmentary pertrochanteric fractures; AO-classification 31-A1 and 31-A2. Both groups were stabilized using the Gamma3® nailing system with and without biodegradable bone cement. Sawbones underwent the same cyclic loading test, simulating 10.000 gait cycles loading the bones with three times body weight. Migration was determined by comparing computed tomography scans recorded before and after the mechanical testing. The three-dimensional migration of the lag screw was calculated, and the rotation of the head around the longitudinal axis was determined. Findings: Biodegradable cement reduced migration by approximately 35% in 31-A1 fractures (25.4% in 31-A2 fractures) and the rotation of the head around the lag screw by approximately 37% in 31-A1 fractures (17.8%, 31-A2). Interpretation: Use of biodegradable bone cement improved the primary stability of gamma nail osteosynthesis in the biomechanical model. Highlights: Biomechanical in vitro study to validate augmentation of gamma-nail with biodegradable cement. Improved compound of osteosynthesis by application of biodegradable cement in the femoral head. Additive use of biodegradable cement can reduce the risk of cut-out in unstable femur fractures.